Pengajaran Bahasa Inggris Berbasis Diferensiasi dengan Metode Pembelajaran Tutor Sebaya di UPT SPF SMPN 3 Makassar - Anggreni, Sulastri Putri; Khaerani, Raisa Nurul; Asriati; Munir; La Sunra (Jurusan Bahasa Inggris, 2024)
The implementation of the Merdeka Curriculum presents student-centered learning with a differentiated system that recognizes the different needs and abilities of each student. Peer tutoring is a learning method that can be used in this learning, where students help each other learn the material. Students are divided into three groups based on their level of understanding to discuss together and work on different assignments for each group. The results showed that some students increased their self-confidence and motivation, and were able to catch up in completing their LKPD or LKS assignments.